Marine Archaeon Methanosarcina acetivorans Enhances Polyphosphate Metabolism Under Persistent Cadmium Stress - Jasso-Chávez, Ricardo; Lira-Silva, Elizabeth; González-Sánchez, Kasia; Larios-Serrato, Violeta; Mendoza-Monzoy, Diana Lucía; Pérez-Villatoro, Fernando; Morett, Enrique; Vega-Segura, Alicia; Torres-Márquez, M. Eugenia; Zepeda-Rodríguez, Armando; Moreno-Sánchez, Rafael (Frontiers in Microbiology, 2019)
Phosphate metabolism was studied to determine whether polyphosphate (polyP) pools play a role in the enhanced resistance against Cd2+ and metal-removal capacity of Cd2+-preadapted (CdPA) Methanosarcina acetivorans. Polyphosphate kinase (PPK), exopolyphosphatase (PPX) and phosphate transporter transcript levels and their activities increased in CdPA cells compared to control (Cnt) cells. K+ inhibited recombinant Ma-PPK and activated Ma-PPX, whereas divalent cations activated both enzymes. Metal-binding polyP and thiol-containing molecule contents, Cd2+-removal, and biofilm synthesis were significantly higher in CdPA cells>Cnt cells plus a single addition of Cd2+>Cnt cells. Also, CdPA cells showed a higher number of cadmium, sulfur, and phosphorus enriched-acidocalcisomes than control cells. Biochemical and physiological phenotype exhibited by CdPA cells returned to that of Cnt cells when cultured without Cd2+. Furthermore, no differences in the sequenced genomes upstream and downstream of the genes involved in Cd2+ resistance were found between CdPA and Cnt cells, suggesting phenotype loss rather than genome mutations induced by chronic Cd2+-exposure. Instead, a metabolic adaptation induced by Cd2+ stress was apparent. The dynamic ability of M. acetivorans to change its metabolism, depending on the environmental conditions, may be advantageous to remove cadmium in nature and biodigesters.